Protective ventilation with high versus low positive end-expiratory pressure during one-lung ventilation for thoracic surgery (PROTHOR): study protocol for a randomized controlled trial - T. Kiss; J. Wittenstein; C. Becker; K. Birr; G. Cinnella; E. Cohen; M. R. El Tahan; L. F. Falcão; C. Gregoretti; M. Granell; T. Hachenberg; M. W. Hollmann; et al. (Trials, 2019)
Abstract Background Postoperative pulmonary complications (PPC) may result in longer duration of in-hospital stay and even mortality. Both thoracic surgery and intraoperative mechanical ventilation settings add considerably to the risk of PPC. It is unclear if one-lung ventilation (OLV) for thoracic surgery with a strategy of intraoperative high positive end-expiratory pressure (PEEP) and recruitment maneuvers (RM) reduces PPC, compared to low PEEP without RM. Methods PROTHOR is an international, multicenter, randomized, controlled, assessor-blinded, two-arm trial initiated by investigators of the PROtective VEntilation NETwork. In total, 2378 patients will be randomly assigned to one of two different intraoperative mechanical ventilation strategies. Investigators screen patients aged 18 years or older, scheduled for open thoracic or video-assisted thoracoscopic surgery under general anesthesia requiring OLV, with a maximal body mass index of 35 kg/m2, and a planned duration of surgery of more than 60 min. Further, the expected duration of OLV shall be longer than two-lung ventilation, and lung separation is planned with a double lumen tube. Patients will be randomly assigned to PEEP of 10 cmH2O with lung RM, or PEEP of 5 cmH2O without RM. During two-lung ventilation tidal volume is set at 7 mL/kg predicted body weight and, during OLV, it will be decreased to 5 mL/kg. The occurrence of PPC will be recorded as a collapsed composite of single adverse pulmonary events and represents the primary endpoint. Discussion PROTHOR is the first randomized controlled trial in patients undergoing thoracic surgery with OLV that is adequately powered to compare the effects of intraoperative high PEEP with RM versus low PEEP without RM on PPC. The results of the PROTHOR trial will support anesthesiologists in their decision to set intraoperative PEEP during protective ventilation for OLV in thoracic surgery. Trial registration The trial was registered in clinicaltrials.gov (NCT02963025) on 15 November 2016.